2017
DOI: 10.1037/abn0000249
|View full text |Cite
|
Sign up to set email alerts
|

Altered experiential, but not hypothetical, delay discounting in schizophrenia.

Abstract: Delay discounting (DD) is a future-oriented decision making process that refers to whether one is willing to forego a smaller, sooner reward for the sake of a larger, later reward. It can be assessed using hypothetical tasks, which involve choices between hypothetical rewards of varying amounts over delay periods of days to years, or experiential tasks, which involve receiving actual rewards in real time over delay periods of seconds to minutes. Initial studies in schizophrenia have only used hypothetical task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 73 publications
(138 reference statements)
1
18
0
Order By: Relevance
“…Several previous studies have compared discounting in experienced delay tasks (as in our short tasks) with tasks where delays were hypothetical or just one was experienced (Johnson and Bickel, 2002; Lane et al, 2003; Reynolds and Schiffbauer, 2004; Navarick, 2004; Horan et al, 2017). For example, Lane et al (2003), also used a within-subject design to examine short vs. long delays (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have compared discounting in experienced delay tasks (as in our short tasks) with tasks where delays were hypothetical or just one was experienced (Johnson and Bickel, 2002; Lane et al, 2003; Reynolds and Schiffbauer, 2004; Navarick, 2004; Horan et al, 2017). For example, Lane et al (2003), also used a within-subject design to examine short vs. long delays (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, growing evidence from behavioral economics provides support for the view that discounting over a given time delay changes with the time-horizon (Berns et al, 2007; Andreoni et al, 2015). Among human studies comparing short and long time-horizons only a few are within subject and incentivized, leaving this matter unresolved (Paglieri, 2013; Johnson et al, 2015; Vanderveldt et al, 2016; Horan et al, 2017). Yet, there remains debate in the empirical economics literature about how well discounting measures elicited in human studies truly reflect the rates of time-preference used in real-world decisions since measured discount rates have been found to vary by the type of task (hypothetical, potentially real, and real), stakes being compared, age of participants and across different domains (Chapman and Elstein, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…To increase the validity of the data analysis and the results for the delay discounting task, two widely used criteria (Horan et al, 2017;Tian et al, 2018;Wilson et al, 2011) were applied to identify unsystematic data (see Supplementary materials for details). Participants whose data under each emotional condition that met both criteria were considered unsystematic and excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating delay discounting in patients with schizophrenia have produced inconsistent results. Some studies found that patients with schizophrenia exhibited greater delay discounting than healthy controls (Heerey et al, 2011;Yu et al, 2017;Weller et al, 2014), while others did not (Horan et al, 2017;MacKillop and Tidey, 2011;Wing et al, 2012). A functional magnetic resonance imaging (fMRI) study has shown that patients with schizophrenia had abnormal activation in the insula, the cingulate gyrus, the precuneus and the ventral striatum in a delay discounting task (Avsar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined DD performance in SZ. Most have found that individuals with SZ have steeper discounting rates than healthy controls (Ahn et al, 2011; Avsar et al, 2013; Brown, Hart, Snapper, Roffman, & Perlis, 2018; Heerey et al, 2007; Weller et al, 2014; Yu et al, 2017); however, findings have not been consistent across all studies (Horan, Johnson, & Green, 2017; Kirschner et al, 2016; MacKillop & Tidey, 2011; Wang et al, 2018; Wing, Moss, Rabin, & George, 2012). Neuroimaging studies indicate that steeper discounting is associated with aberrant activation in brain regions associated with executive function (inferior frontal gyri, dorsal anterior cingulate cortex, posterior parietal cortex) and reward processing (ventral striatum and mid-brain) (Avsar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%